Light olefins synthesis from CO2 hydrogenation over mixed Fe–Co–K supported on micro-mesoporous carbon catalysts. (30th December 2022) - Witoon, Thongthai; Numpilai, Thanapha; Nueangnoraj, Khanin; Cheng, Chin Kui; Chareonpanich, Metta; Limtrakul, Jumras
Abstract: Recycling CO2 into light olefins is a promising approach to reduce CO2 emissions. To promote this technology, an efficient catalyst with high activity and selectivity towards light olefins is imperative. In this work, a series of Fe–Co–K supported on micro-mesoporous carbon (MMC) and microporous carbon (MC) with different metal loading contents (20–80 wt%) were prepared for CO2 hydrogenation to light olefins. Impregnating mixed metal oxides on both MMC and MC reduced particle sizes and enhanced their dispersion and reducibility, yielding a higher CO2 conversion compared to the unsupported Fe–Co–K catalyst. The metal oxides were highly dispersed inside the micropores of MC support, achieving the highest CO2 conversion. However, the high dispersion of metal oxides inside micropores led to the formation of isolated particles with a low interfacial contact with each other, resulting in a low light olefins selectivity. The MMC support provided a lower degree of metal dispersion, creating more interfacial contact area, promoting the selectivity towards olefins. Overall, the 60 wt% Fe–Co–K supported on MMC catalyst exhibited the highest light olefins yield of 10.8% at 400 °C and 20 bar and excellent stability. Graphical abstract: Image 1 Highlights: Fe–Co–K loaded on microporous and micro-mesoporous carbon supports. Micropores confined particle sizes of metal oxides and level of aggregates. Mesopores allowed aggregates of metal oxides providing an intimate contact of particles. Fe–Co–K supported on microporous carbon produced a high fraction of CH4 . Fe–Co–K supported on micro-mesoporous carbon provided a high light olefins yield.